New triazepine carboxylate derivatives: correlation between corrosion inhibition property and chemical structure - Alaoui, K.; El Kacimi, Y.; Galai, M.; Serrar, H.; Touir, R.; Kaya, S.; Kaya, C. (International Journal of Industrial Chemistry, 2023)
In this investigation, attempts have been made to study the corrosion inhibition properties of three new triazepine carboxylate compounds for mild steel in 1.0 M hydrochloric acid medium. The evaluation was carried out using mass loss, electrochemical impedance spectroscopy and polarization curves measurement. Impedance diagrams and Bode plots for uninhibited and inhibited systems were analyzed using Zview program. The fitted data observed trails in nearly the same pattern as the experimental results. It is showed that triazepine carboxylate compounds are very good inhibitors for mild steel corrosion in 1.0 M hydrochloric acid medium which act as mixed-type inhibitors. So, the inhibition efficiency was increased with inhibitor concentration in the order ClâMeâCNâ>âMeâCNâ>âClâMeâCO2Et which depended on their molecular structures. Electrochemical impedance spectroscopy showed that all compounds act by the formation of a protective film at the metal surface. Surface analyses via SEM and Optical 3D profilometry were used to investigate the morphology of the steels before and after immersion in 1.0 M HCl solution containing inhibitors. The correspondence between inhibition property and molecular structure of the triazepine carboxylate compounds was investigated, using density functional theory (DFT). Experimental and DFT study was further supported by molecular dynamic simulations study.